Between Past and Future: Reflections on the New Interpretation of Borys Hrіnchenko's Educational Ideas (the late nineteenth - early twentieth centuries) - Olena Budnyk (Vasyl Stefanyk Precarpathian National University, 2024)
The research dives into similarities between historical events in the early twentieth and twenty-first centuries, drawing connections to Borys Hrinchenko's inspirations which resonate with contemporary efforts in resisting russian occupation, emphasizing the struggle for Ukrainian independence, identity, and freedom through primarily ideological, cultural, national, and linguistic means. The article highlights the leading pedagogical ideas of the scientific and journalistic heritage of Borys Hrinchenko, a prominent Ukrainian linguist, writer, poet, playwright, publicist, critic, ethnographer, educator, and public figure of the late nineteenth - early twentieth centuries. The author focuses on various aspects of the scientist's contributions, including ethnographic research and methodological systematization of Ukrainian folk art, social endeavors aimed at common societal objectives, educational perspectives, and pedagogical intentions. Additionally, the emphasis is on humanizing personal and social interactions among individuals through the promotion of universal moral ideals and spiritual values, among other aspects. The article provides characteristics of educational concepts related to the national upbringing of Ukrainian youth within Borys Hrinchenko's scientific and journalistic heritage. It outlines the pedagogical discussions on intergenerational transmission in the realm of Ukrainian studies during the specified period. The author attempts to reinterpret the eminent thinker's persona in intrinsic harmony with well-known figures from the intellectual elite of that era. Significant attention is devoted to the alignment of creative concepts between Borys Hrinchenko and Ivan Franko. The article highlights Kamenyar's extensive praise for Hrinchenko, mentioning his resilience challenging criticism, often hostile, and his consistent profound love for Ukraine and "sincere democracy" in all his writings. Specific examples are presented to illustrate Hrinchenko's aimed critique of Khrystyna Alchevska's idleness, particularly in the context of russifying Ukrainian schools and publishing her books in russian. The research offers an entirely different interpretation of the critical perspective on certain intellectuals' scientific and literary works from the relevant period. This perspective was aimed at the promotion of Ukrainian studies and national education. The article explores certain aspects of Hrinchenko's role as a teacher in a rural school, drawing from historical and scholarly references. It emphasizes the strong connection between two generations of the Ukrainian national movement - Borys Hrinchenko and Dmytro Doroshenko - by analyzing their common efforts. The author highlights their effective collaboration in developing the Ukrainian independent press, public engagement, educational initiatives, and shaping the Ukrainian people's national consciousness and identity.